Between the cosmopolitan and the parochial: the immigrant gentrifier in Koreatown, Los Angeles. (2nd January 2019) - DeVerteuil, Geoff; Yun, Ohsoon; Choi, Carolyn
Abstract: This paper questions the currently lopsided relationship between the cosmopolitan and the parochial, in which the former is favored both conceptually and empirically. In response, we propose a relational framework for bringing them into conversation, simultaneously recasting and re-animating longstanding debates via three framing devices – the process of relationality/territoriality, disposition, and spaces of encounter – embedded in and through the subject of the immigrant-gentrifier in Koreatown, Los Angeles, itself a novel category that has hitherto eluded systematic research. We present the results of 25 interviews of Korean immigrant-gentrifiers and 10 key informant interviews. The results constitute a parochial critique that emerges as a series of conflicted paradoxes but also productive tensions: between an ostensibly transnational process compromised by a profoundly homegrown, parochial set of investors and outlooks; between a set of dispositions that seek inner-city diversity and density, yet simultaneously sheltered from its spillover costs; and spaces of encounter marked by a gap between the promise of truly open spaces and the reality of guarded and self-segregated ones. Ultimately, this paper does double duty – conceptually rebalancing the cosmopolitan-parochial relationship, but in doing so empirically elevating the emergence of the understudied immigrant-gentrifier category.